Charge mentale et violence domestique: une approche des récits de femmes en termes de small stories - Mildorf, Jarmila (Récits de la charge mentale des femmes: small stories II)

Design Decisions in the Architecture Development of Advanced Systems: Towards traceable and sustainable Documentation and Communication - Pfeifer, Stefan; Akgül, Didem; Röbenack, Silke; Tihlarik, Amelie; Albert, Bruno; Anacker, Harald; Dumitrescu, Roman (DS 118: Proceedings of NordDesign 2022)

Design of an optimised value creation network for zero emission ferries - Disselkamp, Jan-Philipp; Seidenberg, Tobias; Anacker, Harald; Dumitrescu, Roman (Proceedings of the IEEE)

Knowledge-based Interactive Configuration Tool for Industrial Augmented Reality Systems - Eckertz, Daniel; Anacker, Harald; Dumitrescu, Roman (Proceedings of the 5th International Conference on Information and Computer Technologies (ICICT))

Towards a Process Model to Enable Domain Experts to Become Citizen Data Scientists for Industrial Applications - Merkelbach, Silke; von Enzberg, Sebastian; Kuhn, Arno; Dumitrescu, Roman (Proceedings of the IEEE)

Systematics for the individual assessment of augmented reality potentials to support product validation - Eckertz, Daniel; Anacker, Harald; Dumitrescu, Roman (Proceedings of NordDesign 2022)

Implementation of Systems Engineering: A maturity-based approach - Wilke, Daria; Pfeifer, Stefan; Heitmann, Rebecca; Anacker, Harald; Dumitrescu, Roman; Franke, Volker (Proceedings of the IEEE ISSE)

Experimentelle Untersuchung des Ermüdungsverhaltens und Berechnung der Lebensdauer von Stahlklebverbindungen bei multiaxialer Belastung - Tews, Karina; Teutenberg, Dominik; Meschut, Gerson

Fridolin-Duck Karotti. Mit einem kollaborativen Schreibtool gemeinsam Fantasiere beschreiben - Rezat, Sara; Scholle, Oliver; Bendner, Sarah (Praxis Deutsch 292)

Improved output gap estimates and forecasts using a local linear regression - Fritz, Marlon (International Economics)
Keywords: General Economics; Econometrics and Finance; General Business; Management and Accounting

Digital lesen und schreiben. Basisbeitrag - Rezat, Sara (Praxis Deutsch)

Second-harmonic generation in atomically thin 1T−TiSe2 and its possible origin from charge density wave transitions - Zhang, Ruiming; Ruan, Wei; Yu, Junyao; Gao, Libo; Berger, Helmuth; Forró, László; Watanabe, Kenji; Taniguchi, Takashi; Ranjbar, Ahmad; Belosludov, Rodion V.; Kühne, Thomas; Bahramy, Mohammad Saeed; et al. (Physical Review B)

Electronic Structures of Group III–V Element Haeckelite Compounds: A Novel Family of Semiconductors, Dirac Semimetals, and Topological Insulators - Khazaei, Mohammad; Ranjbar, Ahmad; Kang, Yoon‐Gu; Liang, Yunye; Khaledialidusti, Rasoul; Bae, Soungmin; Raebiger, Hannes; Wang, Vei; Han, Myung Joon; Mizoguchi, Hiroshi; Bahramy, Mohammad S.; Kühne, Thomas; et al. (Advanced Functional Materials)
Keywords: Electrochemistry; Condensed Matter Physics; Biomaterials; Electronic; Optical and Magnetic Materials

Real-Space Identification of Non-Noble Single Atomic Catalytic Sites within Metal-Coordinated Supramolecular Networks - Schulze Lammers, Bertram; López-Salas, Nieves; Stein Siena, Julya; Mirhosseini, Hossein; Yesilpinar, Damla; Heske, Julian Joachim; Kühne, Thomas; Fuchs, Harald; Antonietti, Markus; Mönig, Harry (ACS Nano)
Keywords: General Physics and Astronomy; General Engineering; General Materials Science

On the Role of Hydrogen Bond Strength and Charge Transfer of a Diels-Alder Reaction On-Water: Semiempirical and Free Energy Calculations. - Henao Aristizabal, Andres; Gohar, Yomna; Whilhelm, René; Kühne, Thomas
Accelerated chemistry at the interface with water has received increasing attention. The mechanisms behind the enhanced reactivity On-Water are not yet clear. In this work we use a Langevin scheme in the spirit of second generation Car-Parrinello to accelerate the second-order density functional Tight-Binding (DFTB2) method in order to investigate the free energy of two Diels-Alder reaction On-Water: the cycloaddition between cyclopentadiene and ethyl cinnamate or thionocinnamate. The only difference between the reactants is the substitution of a carbonyl oxygen for a thiocarbonyl sulfur, making possible the distinction between them as strong and weak hydrogen-bond acceptors. We find a different mechanism for the reaction during the transition states and uncover the role of hydrogen bonds along with the reaction path. Our results suggest that acceleration of Diels-Alder reactions do not arise from an increased number of hydrogen bonds at the transition state and charge transfer plays a significant role. However, the presence of water and hydrogen-bonds is determinant for the catalysis of these reactions.

CENT2: Improved charge equilibration via neural network technique - Khajehpasha, Ehsan Rahmatizad; Finkler, Jonas A.; Kühne, Thomas; Ghasemi, Alireza (Physical Review B)

Surface Passivation and Detrimental Heat-Induced Diffusion Effects in RbF-Treated Cu(In,Ga)Se2 Solar Cell Absorbers - Elizabeth, Amala; Sahoo, Sudhir K.; Phirke, Himanshu; Kodalle, Tim; Kühne, Thomas; Audinot, Jean-Nicolas; Wirtz, Tom; Redinger, Alex; Kaufmann, Christian A.; Mirhosseini, Hossein; Mönig, Harry (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Fingerprints Indicating Superior Properties of Internal Interfaces in Cu(In,Ga)Se 2 Thin‐Film Solar Cells - Raghuwanshi, Mohit; Chugh, Manjusha; Sozzi, Giovanna; Kanevce, Ana; Kühne, Thomas; Mirhosseini, Hossein; Wuerz, Roland; Cojocaru‐Mirédin, Oana (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Do Lead Halide Hybrid Perovskites Have Hydrogen Bonds? - Ibaceta-Jaña, Josefa; Chugh, Manjusha; Novikov, Alexander S.; Mirhosseini, Hossein; Kühne, Thomas; Szyszka, Bernd; Wagner, Markus R.; Muydinov, Ruslan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian Joachim; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas; Antonietti, Markus; López-Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Time resolved THz-Raman spectroscopy reveals that cations and anions distinctly modify intermolecular interactions of water - Balos, Vasileios; Kaliannan, Naveen Kumar; Elgabarty, Hossam; Wolf, Martin; Kühne, Thomas; Sajadi, Mohsen

Who has the future in mind? Gender, time perspectives, and pro-environmental behaviour - Hoffmann, Christin; Hoppe, Julia Amelie; Ziemann, Niklas (Environmental Research Letters)
Abstract An individual’s relation to time may be an important driver of pro-environmental behaviour. We studied whether young individual’s gender and time-orientation are associated with pro-environmental behaviour. In a controlled laboratory environment with students in Germany, participants earned money by performing a real-effort task and were then offered the opportunity to invest their money into an environmental project that supports climate protection. Afterwards, we controlled for their time-orientation. In this consequential behavioural setting, we find that males who scored higher on future-negative orientation showed significantly more pro-environmental behaviour compared to females who scored higher on future-negative orientation and males who scored lower on future-negative orientation. Interestingly, our results are completely reversed when it comes to past-positive orientation. These findings have practical implications regarding the most appropriate way to address individuals in order to achieve more pro-environmental behaviour.
Keywords: Public Health; Environmental and Occupational Health; General Environmental Science; Renewable Energy; Sustainability and the Environment

Künstliche Intelligenz in der industriellen Arbeitswelt - Studie zum Status Quo in der Region OstWestfalenLippe - Papenkordt, Jörg; Gabriel, Stefan; Thommes, Kirsten; Dumitrescu, Roman
Im Rahmen dieser Studie wird der Status Quo des KI-Einsatzes in der industriellen Arbeitswelt in der Region OstWestfalenLippe erfasst und beschrieben. Dadurch wird eine Grundlage geschaffen, um eine zielführende Unterstützung der Gestaltung von durch Künstliche Intelligenz (KI) gestützter Arbeitsprozesse in Unternehmen zu ermöglichen, indem beispielsweise bedarfsbezogene Maßnahmen entwickelt und durchgeführt sowie weiterer Forschungsbedarf aufgezeigt wird. Die Befragung wurde im Jahr 2021 von dem Kompetenzzentrum Arbeitswelt.Plus sowie dem Spitzencluster it’s OWL initiiert. Dabei sind drei Zielgruppen – Unternehmensleitung, Personalabteilung (HR) sowie Arbeitnehmer*innen – adressiert worden. Insgesamt nahmen 317 Personen aus 89 verschiedenen Unternehmen bzw. Organisationen an der Befragung teil – zu 38 % Unternehmer*innen, zu 13 % Personaler*innen und zu 49 % Arbeitnehmer*innen. Die meisten der Teilnehmenden stammten aus der Elektroindustrie, dem Maschinenbau sowie dem Informations- und Kommunikationstechnologie (IKT)-Sektor. Die Befragungsergebnisse zeigen, dass sich die meisten Unternehmen in der Anfangsphase der KI-Nutzung befinden. Zwischen einzelnen Unternehmensbereichen und verschiedenen Branchen zeigen sich gewisse Unterschiede in der Nutzungsphase. Die Befragten stehen aktuell vor der Nutzung von vor allem teilautonomen KI-Systemen, die ausführende und analytische menschliche Tätigkeitenbeispielsweise durch Informationsbereitstellungen unterstützen. Wesentliche Ziele der KI-Nutzung sind die Effizienzsteigerung, Qualitätsverbesserung, Entscheidungsoptimierung sowie Unterstützung der Arbeitnehmer*innen. Allerdings werden in allen Unternehmen die fehlende Expertise sowie insgesamt die Komplexität des Themenfelds als Hinderungsgründe identifiziert. In allen Unternehmen und allen Unternehmensbereichen werden hohe Auswirkungen durch KI erwartet. Auf die Arbeitsgestaltung werden insgesamt eher positive Auswirkungen erwartet. Die Befragten schätzen die Bedeutung von KI, ihre Aufgeschlossenheit sowie ihr Vertrauen gegenüber KI als insgesamt hoch ein, ihr Verständnis von KI dagegen eher als gering. Tendenziell zeigt sich eine große Diskrepanz zwischen Selbst- und Fremdbild mit einer teils deutlich negativeren Wahrnehmung anderer. Die Befragten erwarten außerdem steigende Kompetenzanforderungen sowie einen hohen Weiterbildungsbedarf, insbesondere bezüglich des grundlegenden Verständnisses über KI. In den wenigsten Unternehmen existiert jedoch ein gezieltes Weiterbildungsangebot. Die Erkenntnisse aus der Befragung fließen im Rahmen des Kompetenzzentrums Arbeitswelt.Plus in die gezielte Gestaltung und Einführung KI-gestützter Arbeitsformen sowie bedarfsgerechter Unterstützungsangebote ein. Die hohe Komplexität der KI-Einführung sowie die sowohl technischen als auch mitarbeiterbezogenen Herausforderungen verdeutlichen den Bedarf für eine soziotechnische Perspektive und ein systematisches Vorgehen bei der Gestaltung dieses vielschichtigen Themenfelds.

Künstliche Intelligenz im Engineering - Kharatyan, Aschot; Humpert, Lynn; Anacker, Harald; Dumitrescu, Roman; Wäschle, Moritz; Albers, Albert; Horstmeyer, Sarah (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Künstliche Intelligenz bietet großes Potenzial im Engineering. Der Einsatz gestattet insbesondere für Wissensarbeiter eine effiziente Arbeitsteilung, in der beispielsweise fehleranfällige und repetitive Aktivitäten unterstützt werden. Eine erfolgreiche Einführung bedarf einer vorangehenden Analyse von nutzenstiftenden Einsatzpotenzialen, bei der alle Anwendenden frühzeitig einbezogen werden. Der folgende Beitrag verdeutlicht dieses Vorgehen anhand eines realen Beispiels im Sondermaschinenbau.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Planning the Analysis of Use Phase Data in Product Planning - Meyer, Maurice; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The ongoing digitalization of products offers product managers new potentials to plan future product generations based on data from the use phase instead of assumptions. However, product managers often face difficulties in identifying promising opportunities for analyzing use phase data. In this paper, we propose a method for planning the analysis of use phase data in product planning. It leads product managers from the identification of promising investigation needs to the derivation of specific use cases. The application of the method is shown using the example of a manufacturing company.

How can Data Analytics Results be Exploited in the Early Phase of Product Development? 13 Design Principles for Data-Driven Product Planning - Meyer, Maurice; Fichtler, Timm; Koldewey, Christian; Dumitrescu, Roman (AMCIS 2022 Proceedings)
The megatrend digitalization turns mechatronic products into continuous collectors and generators of use phase data. By analyzing this data, manufacturers can uncover valuable insights about the products and the users. Especially in product planning, these insights could be used to plan promising future product generations. The systematic exploitation of data analytics results, however, represents a serious challenge, as research on the topic is still scarce. In this paper, we present 13 design principles for exploiting data analytics results in product planning. The results are based on a systematic literature review and a workshop with a research consortium. The evaluation of the design principles is demonstrated with a real case of a manufacturing company. The identified design principles represent a first contribution to a still scarcely explored research field.

17 Use Cases for Analyzing Use Phase Data in Product Planning of Manufacturing Companies - Meyer, Maurice; Panzner, Melina; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Model-based Analysis and Specification of Functional Requirements and Tests for Complex Automotive Systems - Wiecher, Carsten; Mandel, Constantin; Günther, Matthias; Fischbach, Jannik; Greenyer, Joel; Greinert, Matthias; Wolff, Carsten; Dumitrescu, Roman; Mendez, Daniel; Albers, Albert (arXiv preprint)

Evaluation of Industry 4.0 Applications in Production - Joppen, Robert; Kühn, Arno; Förster, Magdalena; Dumitrescu, Roman (Journal of the Knowledge Economy)
Abstract Industry 4.0 promises many potentials in production. Examples are a data-driven optimization of production processes of individual machines, driverless transport systems, and assistance systems. Nevertheless, companies are still hesitant to invest in Industry 4.0 applications. Studies show that one of the main reasons for that is the unclear economic benefit. In this work, we present a systematic approach for the evaluation of Industry 4.0 applications in production. The main goal of the systematic is to create transparency over the evaluation process of an investment in an Industry 4.0 application in production. The evaluation of a concrete technical solution in an existing production system is supported. As a theoretical foundation, a characterization of investments in Industry 4.0 applications is given. From that, a procedure model is derived. It puts the activities to be carried out, the tools to be used and results in a temporal context. The application of the systematic is shown on the basis of an application example.
Keywords: Economics and Econometrics

Collaborative Modeling of Use Case & Damage Scenarios in Online Workshops Using a 3D Environment - Japs, Sergej; Schmidt, Sebastian; Kargl, Frank; Kaiser, Lydia; Kharatyan, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The development of technical systems requires close cooperation of stakeholders from different disciplines. This collaboration takes place in workshops. Driven by digitalization and by the current pandemic such workshops take place primarily online. Suitable collaboration tools and methods are crucial to success. At the beginning of such workshops, use and damage scenarios are identified. In this paper, we presented a method and tool for identifying and modeling use and damage scenarios, which we evaluated in 14 online workshops with a total of 118 participants over a period of almost 3 years.

Why make it hard? - Usage of aggregated statistical data for risk assessment of damage scenarios in the context of ISO/SAE 21434 - Japs, Sergej; Kargl, Frank; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Efficient method for determining substrate parameters of additive manufactured spatial circuit carriers - Mager, Thomas; Jürgenhake, Christoph; Dumitrescu, Roman (2022 14th German Microwave Conference (GeMiC))

Use Case Driven Digital Twin Generation - Gollner, Denis; Klausmann, Tobias; Rasor, Rik; Dumitrescu, Roman (2022 IEEE 5th International Conference on Industrial Cyber-Physical Systems (ICPS))

Requirements analysis for an intelligent workforce planning system: a socio-technical approach to design AI-based systems - Gabriel, Stefan; Bentler, Dominik; Grote, Eva-Maria; Junker, Caroline; Wendischhoff, David Meyer zu; Bansmann, Michael; Latos, Benedikt; Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Cross-industry methods for strategic planning of the digital transformation of small and medium sized enterprises - Förster, Magdalena; Kürpick, Christian; Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Security- and Safety-Driven Functional Architecture Development Exemplified by Automotive Systems Engineering - Kharatyan, Aschot; Günther, Matthias; Anacker, Harald; Japs, Sergej; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Method for direct end customer integration into the agile product development - Humpert, Lynn; Röhm, Benjamin; Anacker, Harald; Dumitrescu, Roman; Anderl, Reiner (Procedia CIRP)
Keywords: General Medicine

Development of a Numerical 3D Model for Analyzing Clinched Joints in Versatile Process Chains - Bielak, C. R.; Böhnke, M.; Bobbert, M.; Meschut, G. (The Minerals, Metals & Materials Series)

EvoLearner: Learning Description Logics with Evolutionary Algorithms - Heindorf, Stefan; Blübaum, Lukas; Düsterhus, Nick; Werner, Till; Golani, Varun Nandkumar; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (WWW)
Classifying nodes in knowledge graphs is an important task, e.g., predicting missing types of entities, predicting which molecules cause cancer, or predicting which drugs are promising treatment candidates. While black-box models often achieve high predictive performance, they are only post-hoc and locally explainable and do not allow the learned model to be easily enriched with domain knowledge. Towards this end, learning description logic concepts from positive and negative examples has been proposed. However, learning such concepts often takes a long time and state-of-the-art approaches provide limited support for literal data values, although they are crucial for many applications. In this paper, we propose EvoLearner - an evolutionary approach to learn ALCQ(D), which is the attributive language with complement (ALC) paired with qualified cardinality restrictions (Q) and data properties (D). We contribute a novel initialization method for the initial population: starting from positive examples (nodes in the knowledge graph), we perform biased random walks and translate them to description logic concepts. Moreover, we improve support for data properties by maximizing information gain when deciding where to split the data. We show that our approach significantly outperforms the state of the art on the benchmarking framework SML-Bench for structured machine learning. Our ablation study confirms that this is due to our novel initialization method and support for data properties.

Verhandlungen sexueller und kultureller Fremd- und Selbstbestimmungen in Kristina Aamand’s interkulturellem Adoleszenzroman „Wenn Worte meine Waffe wären“ - Zierau, Cornelia; Kofer, Martina (Interkulturelles Lernen mit Kinder- und Jugendliteratur (in Vorbereitung))

Wertorientierung und Werteverhandlungen in Emine Sevgi Özdamars Roman „Das Leben ist eine Karawanserei“ - Zierau, Cornelia (Türkisch-deutsche Studien Jahrbuch 2020: Wertorientierungen)

Türkisch-deutsche Studien Jahrbuch 2020: Wertorientierungen

Increasing Firm Performance through Industry 4.0—A Method to Define and Reach Meaningful Goals - Koldewey, Christian; Hobscheidt, Daniela; Pierenkemper, Christoph; Kühn, Arno; Dumitrescu, Roman (Sci)

Collaborative Modeling of Interoperable Digital Twins in a SoS Context - Göllner, Denis; Rasor, Rik; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Potentials and challenges of analyzing use phase data in product planning of manufacturing companies - Meyer, Maurice; Fichtler, Timm; Koldewey, Christian; Dumitrescu, Roman (Artificial Intelligence for Engineering Design, Analysis and Manufacturing)
The successful planning of future product generations requires reliable insights into the actual products’ problems and potentials for improvement. A valuable source for these insights is the product use phase. In practice, product planners are often forced to work with assumptions and speculations as insights from the use phase are insufficiently identified and documented. A new opportunity to address this problem arises from the ongoing digitalization that enables products to generate and collect data during their utilization. Analyzing these data could enable their manufacturers to generate and exploit insights concerning product performance and user behavior, revealing problems and potentials for improvement. However, research on analyzing use phase data in product planning of manufacturing companies is scarce. Therefore, we conducted an exploratory interview study with decision-makers of eight manufacturing companies. The result of this paper is a detailed description of the potentials and challenges that the interviewees associated with analyzing use phase data in product planning. The potentials explain the intended purpose and generic application examples. The challenges concern the products, the data, the customers, the implementation, and the employees. By gathering the potentials and challenges through expert interviews, our study structures the topic from the perspective of the potential users and shows the needs for future research.
Keywords: Artificial Intelligence; Industrial and Manufacturing Engineering

EngOps – Ein Leitbild für das agile Zusammenwirken von Engineering und Operations - Anacker, Harald; Dumitrescu, Roman; Michels, Nico; Rasor, Rik (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Um global erfolgreich zu bleiben, wird es bald nicht mehr ausreichen, Kriterien wie ein gutes Produktdesign zu erfüllen. Stattdessen muss der Kundennutzen kontinuierlich über den Produktlebenszyklus hinaus gesteigert werden. Tech-Konzerne verzeichnen bereits Erfolge und verkörpern den Wandel schon heute. Vor diesem Hintergrund ist ein neues Leitbild in der Entwicklung und dem Betrieb von zukünftigen, technischen Systemen erforderlich. EngOps soll diesen Bedarf decken und steht für die agile Kollaboration zwischen Engineering und Operations. Alle Teile des Unternehmens sollen ständig miteinander kooperieren, um so beispielsweise wandelbare Produkte auch nach dem Verkauf entwickeln zu können.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Giant Orbital Anisotropy with Strong Spin–Orbit Coupling Established at the Pseudomorphic Interface of the Co/Pd Superlattice - Kim, Sanghoon; Pathak, Sachin; Rhim, Sonny H.; Cha, Jongin; Jekal, Soyoung; Hong, Soon Cheol; Lee, Hyun Hwi; Park, Sung‐Hun; Lee, Han‐Koo; Park, Jae‐Hoon; Lee, Soogil; Steinrück, Hans-Georg; et al. (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

An In-depth Study of Java Deserialization Remote-Code Execution Exploits and Vulnerabilities - Sayar, Imen; Bartel, Alexandre; Bodden, Eric; Le Traon, Yves (ACM Transactions on Software Engineering and Methodology)
Nowadays, an increasing number of applications uses deserialization. This technique, based on rebuilding the instance of objects from serialized byte streams, can be dangerous since it can open the application to attacks such as remote code execution (RCE) if the data to deserialize is originating from an untrusted source. Deserialization vulnerabilities are so critical that they are in OWASP’s list of top 10 security risks for web applications. This is mainly caused by faults in the development process of applications and by flaws in their dependencies, i.e., flaws in the libraries used by these applications. No previous work has studied deserialization attacks in-depth: How are they performed? How are weaknesses introduced and patched? And for how long are vulnerabilities present in the codebase? To yield a deeper understanding of this important kind of vulnerability, we perform two main analyses: one on attack gadgets, i.e., exploitable pieces of code, present in Java libraries, and one on vulnerabilities present in Java applications. For the first analysis, we conduct an exploratory large-scale study by running 256 515 experiments in which we vary the versions of libraries for each of the 19 publicly available exploits. Such attacks rely on a combination of gadgets present in one or multiple Java libraries. A gadget is a method which is using objects or fields that can be attacker-controlled. Our goal is to precisely identify library versions containing gadgets and to understand how gadgets have been introduced and how they have been patched. We observe that the modification of one innocent-looking detail in a class – such as making it public – can already introduce a gadget. Furthermore, we noticed that among the studied libraries, 37.5% are not patched, leaving gadgets available for future attacks. For the second analysis, we manually analyze 104 deserialization vulnerabilities CVEs to understand how vulnerabilities are introduced and patched in real-life Java applications. Results indicate that the vulnerabilities are not always completely patched or that a workaround solution is proposed. With a workaround solution, applications are still vulnerable since the code itself is unchanged.
Keywords: Software

Fluently specifying taint-flow queries with fluentTQL - Piskachev, Goran; Späth, Johannes; Budde, Ingo; Bodden, Eric (Empirical Software Engineering)

To what extent can we analyze Kotlin programs using existing Java taint analysis tools? - Krishnamurthy, Ranjith; Piskachev, Goran; Bodden, Eric